พฤติกรรมการชมรายการโทรทัศน์กับการนำมาใช้ประโยชน์ในการเรียนการสอนของอาจารย์วิทยาลัยเอกชนในภาคเหนือ - ลำยอง ดวงคำ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objectives of this research were : (1) to study the relationship between television exposure and the uses of television for teaching of private colleges faculties. (2) to study the relationship between the exposure to television programs and the uses of television for teaching. (3) to study the relationship between sex, age, education, teaching experience, faculty and the uses of television programs for teaching. (4) to investigate the factor which could explain the uses of television program for teaching most. The samples were 76 Thai teachers of Yonok College, Lampang province. Questionnaires were used to collect the data. Frequency, percentage, mean, Pearson s Product Moment Correlation Coefficient, t-test, ANOVA and multiple regression analysis were employed for the analysis of the data. SPSS for Windows was used for data processing. The results of the study were as follows; 1. Television exposure correlated with the uses of television programs for teaching. 2. Exposure to television programs correlated with the uses of television for teaching. 3. Teachers different in sex, age, education, teaching experience and faculty used television programs for teaching indifferently. 4. The factor which could explain the uses of television programs for teaching most was the exposure to news program